Impacts of oil palm project on livelihood of the Bidayuh community in Kampung Senah Rayang Darul Ehsan Padawan, Sarawak - Awang Dulhadi, Awang Mat (Universiti Malaysia Sarawak (UNIMAS), 2013)
(Kampung Senah Rayang Darul Ehsan is a Bidayuh village, located in Padawan District, Kuching Sarawak and comprises of 81 households. A study has been carried out to assess the impacts of oil palm establishment on the livelihood among 37 participant families in the studied area. Three specific objectives of the study are (1) To identify the types of changes in the livelihood strategies in relation to the diversification of livelihood strategies and migration, (2) To assess to what extent that the project has given the impacts on income and food security in the studied area and (3) To investigate the effectiveness of Ahli Jawatankuasa Pembangunan Peserta (AJKP) in defending the right of the participant families in the studied area. In order to collect the information for the study, several social science methods were used. These include, key informants interview, in-depth household interview and some PAR/PRA methods. The findings from the study shows that this project failed to improve the households' standards of living. Based on the result obtained, this project failed in stabilizing the households' monthly income. This subsequently, has led to 20 of 25 families understudied diversified their livelihood strategies by retaining their past livelihood as well as reconstructing the new livelihood strategies in order to sustain their living in the area rather than only depending on the benefits from the farm. This project also failed to stop 60 persons of 144 beneficiaries who form 25 participant families understudied from migrating out of Senah Rayang to engage in off-farm employment in the major towns. This because the wages paid by working in the farm and the yearly dividend received from the farm are very low and quite unsustainable. However, this project does not affect the level of income of the participants for most of the months except for the month that they receive dividend from FELCRA which is paid yearly. The project also does not affect the food supply as the area was converted from idle land to oil palm plantation. Apart from that, even though there is a committee that was established by FELCRA Berhad to represent the participants to claim their rights but this committee seen failed in overcoming the main issues that were faced by the participants. These issues include: (1) Unreasonable rate of yearly dividend, (2) Nepotism in the farm as well as (3) The land title issue but this committee was seen failed to play their role effectively. These findings show great contradiction with the goals of land development by the Ministry of Land Development, Sarawak that establishment of oil palm would eradicate poverty, reducing rural-urban migration and increase the standard of living in the rural area